The Moral Mapping of Victorian and Edwardian London: Charles Booth, Christian Charity, and the Poor-but-Respectable - MacKay, Lynn (Labour / Le Travail, 2017)
This article reviews the book, "The Moral Mapping of Victorian and Edwardian London: Charles Booth, Christian Charity, and the Poor-but-Respectable," by Thomas Gibson-Brydon.